Comprehensive Treatment of Patients with Chronic Catarrhal Gingivitis Living in Environmentally Unfavorable Conditions - Pavlyshyn, Mariana; Rozhko, Mykola; Makhlynets, Nataliia; Yatsynovych, Vitalii (Actual Dentistry, 2026)
Background: Chronic catarrhal gingivitis (CCG) in children is influenced by environmental pollution, psycho-emotional stress, and functional impairments in breathing and swallowing. These factors contribute to persistent inflammation and impaired oral hygiene. Objective: To evaluate the effectiveness of comprehensive therapy—including professional oral hygiene, local treatment, and labial-myofunctional rehabilitation using the Froggy Mouth appliance—on periodontal health, breathing patterns, and swallowing function in children living in environmentally unfavorable conditions. Materials and Methods: A total of 120 children aged 12–15 years with CCG were examined and divided into four groups based on their residential environment and treatment protocol. Functional breathing assessment, evaluation of atypical swallowing, and cytomorphometric analysis of periodontal tissues were performed at baseline and during follow-up. Labial-myofunctional therapy using the Froggy Mouth appliance was implemented following adenoidectomy. Local pharmacological therapy was administered according to group assignments. Results: Children residing in environmentally unfavorable regions exhibited higher levels of psycho-emotional stress, poor oral hygiene, and more pronounced cytomorphometric indicators of periodontal inflammation. Functional disorders, including mouth breathing and atypical swallowing, were closely associated with II and IV occlusal patterns. Comprehensive therapy led to a progressive normalization of cytomorphometric parameters and the restoration of functional swallowing skills within a 20–25 week period. Conclusions: CCG in children is significantly exacerbated by stress and environmental factors. Effective management requires an interdisciplinary approach, integrating dental care, ENT intervention, and myofunctional therapy. The Froggy Mouth appliance proved highly effective in restoring swallowing function and improving periodontal health in high-risk pediatric populations.